The Level of Awareness Towards Technopreneurship Dimension Among Faculty Technology Management and Business (FPTP) Students - Azizan, Anim Zalina; Mohd Fatmi Shah, Nurrul Atikah; Kamaruddin, Nor Kamariah (Research in Management of Technology and Business, 2021)
Technopreneurship is a business that involved high technology in developing, deploying and delivering services and solutions that have given new business models, revenues, and economic growth. The problem statements are facing the challenges of the Industrial Revolution 4.0. The critical development of technopreneurship education model in course learning for reducing unemployment mainly from group B40. The Faculty of Technology Management and Business (FPTP) students should have aware of the technopreneurship dimension, which focuses on machines and innovation processes in their learning. The first objective of the research is to find out the dimension of technopreneurship. The second objective is to determine the level of awareness towards the technopreneurship dimension among Faculty Technology Management and Business students. Respondents for this study consisted of the final year BPA program from the Faculty of Technology Management and Business, University of Tun Hussein Onn Malaysia. The study was conducted in quantitative form using a questionnaire instrument for data collection and data were analyzed descriptively using (SPSS). The study found that the awareness of the technopreneurship dimension among the respondent is at a high level. Other than that, the study’s findings show that the mean for the highest level of awareness technopreneurship dimension is self-employment. The results of this study will benefit human society and the country.